A first step to an evidence-based talent identification program in the Netherlands; a research proposal - Faber, I.; Oosterveld, F.; Nijhuis-Van der Sanden, R. (International Journal of Table Tennis Sciences, 2018)
Talent identifications programs are developed for several sports in different countries around the world to improve the chance to excel during important sports events like the Olympics or World Championships. Not only elite sports at world class level but also the recreational level will benefit from talent identification programs. For a small country as The Netherlands, it is desirable to develop a good talent identification program to keep up with international level and to improve the connection between table tennis and recreational sports or non-athletes looking for a sport that fits them well. Because the key-factors which determine talent for table tennis are unknown, research to get a scientific fundament for a talent identification system for table tennis sports is desirable. This article presents along-term research project(PhD)which is set-up by the Dutch Table Tennis Federation(NTTB) together with Saxion University of Applied Sciences and IQ Healthcare of the Radboud University Nijmegen in The Netherlands. The main purpose of this project is to find sport-specific determinants which play a key-role in talent identification in table tennis using a combination of top-down and bottom-up approaches. Preliminary results from the top-down approach are already available from reliability and validity studies on the talent identification assessment (TIDA) which is used by the NTTB. Analysis shows mainly good reliability for the test items separately and for the TIDA as a whole. Concurrent validity is partly confirmed for the TIDA, however further analyses are necessary. This research project can make an important step to an evidence-based talent identification program which benefits table tennis and other sports at elite and recreational level.